Predicting Response of Severe Aplastic Anemia to Rabbit-Antithymocyte Immunoglobulin Based Immunosuppressive Therapy Combined With Eltrombopag - Li, Ruixin; Zhou, Jiongtao; Liu, Zhengyuan; Chen, Xi; Long, Qiqiang; Yang, Yan; Lin, Shengyun; Jia, Jinsong; He, Guangsheng; Li, JianYong (Frontiers in Immunology, 2022)
Addition of eltrombopag (E-PAG) to intensive immunosuppressive therapy (IST) contributes to restoring hematopoiesis in patients with severe aplastic anemia (SAA). Used at relatively low doses in the East Asian population, the efficacies of E-PAG and the predictors for efficacy are not clear. We conducted a retrospective, multicenter study to analyze the efficacy and the possible predicting factors at 6 months in 58 adult SAA patients with rabbit ATG-based IST and E-PAG. The response rates, complete response rates at 6 months were 76%, 21%, respectively. The baseline reticulocyte percentage [area under a curve (AUC)=0.798, 95%CI 0.640-0.956, P=0.006], absolute reticulocyte count (ARC) (AUC =0.808, 95%CI 0.647-0.970, P=0.004), red cell distribution width – coefficient of variation (RDW-CV) (AUC=0.722, 95%CI 0.494-0.950, P=0.040), and absolute lymphocyte count (ALC) (AUC=0.706, 95%CI 0.522-0.890, P=0.057) were highly predictive of response at 6 months. The tipping values of reticulocyte percentage, ARC, RDW-CV and ALC were 0.45%, 7.36×109/L, 11.75% and 1.06×109/L, respectively. The sensitivity and specificity of reticulocyte percentage were 81.6% and 66.7%; ARC were 86.8% and 66.7%, RDW-CV were 94.7% and 55.6%; ALC were 55.3% and 88.9%. At a median follow-up of 15.5 months, the 2-year cumulative overall survival was 92%. The baseline reticulocyte percentage, ARC, RDW-CV and ALC were potential factors to predict a favorable effect of rabbit-ATG based IST plus E-PAG in SAA patients of East Aisan (ChiCTR2100045895).